The effect of Phyllanthus emblica (Amla) fruit supplementation on the rumen microbiota and its correlation with rumen fermentation in dairy cows - Tilahun, Mekonnen; Ma, Lu; Callaway, Todd R.; Xu, Jianchu; Bu, Dengpan (Frontiers in Microbiology, 2024)
Introduction Medicinal plants, rich in phytochemicals like phenolic acids, flavonoids, and tannins, offer potential benefits in enhancing productivity, quality, and animal health. Amla fruit (Phyllanthus emblica) is one such plant with promising attributes. This study aimed to investigate the impact of fresh Amla fruit (FAF) supplementation on ruminal microbial composition and its correlation with rumen fermentation in lactating dairy cows. Methods The study employed a repeated crossover design involving eight ruminally cannulated mid-lactation Holstein dairy cows. Animals received varying levels of fresh Amla fruit supplementation (0, 200, 400, and 600 g/d). Results When 400 g/d of FAF was added to the diet, there was a significant increase in the relative abundance of Firmicutes (p = 0.02). However, at 200 g/d, the relative abundance of ruminal Bacteroidota was higher than the 0 and 400 g/d FAF supplementation (p < 0.01). LEfSe analysis identified distinct taxa, such as Clostridia vadinBB60 in the 200 g/d group, Oscillospiraceae in the 400 g/d group, and Elusimicrobium in the 600 g/d group. Notably, the random forest species abundance statistics identified Oscillospiraceae V9D2013 as a biomarker related to milk yield. Oscillospiraceae, Bacilli RF39, norank_f Prevotellaceae, and Bifidobacterium were positively correlated with ruminal total VFA and molar proportion of propionate, while Rikenellaceae RC9 gut group and Clostridia vadinBB60 were negatively correlated. Discussion FAF supplementation affects the abundance of beneficial microbes in a dose-dependent manner, which can improve milk yield, efficiency, rumen health, desirable fatty acids, and animal health.